Conceptualizing researchers' perspectives on involving professionals in research: a group concept mapping study - Christine E. Laustsen; Albert Westergren; Pia Petersson; Maria Haak (BMC, 2021)
Abstract Background Researchers have shown an increased interest in involving professionals from outside academia in research projects. Professionals are often involved in research on ageing and health when the purpose is to address the gap between research and practice. However, there is a need to acquire more knowledge about what the involvement might lead to by exploring researchers' experiences of involving professionals in research on ageing and health and developing conceptual areas. Therefore, the aim of this study was to identify conceptual areas of professionals' involvement in research on ageing and health, from the perspective of researchers themselves. Methods Group concept mapping, a participatory and mixed method, was used to conceptualize areas. Researchers with experience of involving professionals in research projects on ageing and health participated in qualitative data collection through brainstorming sessions (n = 26), and by sorting statements (n = 27). They then took part in quantitative data collection, where they rated statements according to how much a statement strengthened research (n = 26) and strengthened practice (n = 24). Data were analysed using multidimensional scaling analysis and hierarchical cluster analysis. In addition, a qualitative analysis of the latent meaning of the cluster map was conducted. Results Analysis of the sorting stage generated five clusters illustrating conceptual areas of professionals' involvement in research projects on ageing and health. The five clusters are as follows: complex collaboration throughout the research process; adaptation of research to different stakeholders, mutual learning through partnership; applicable and sustainable knowledge; legitimate research on ageing and health. The qualitative latent meaning of the cluster map showed two themes: the process of involvement and the outcome of involvement. A positive strong correlation (0.87) was found between the rating of strengthened research and practice. Conclusions This study reveals conceptual areas on a comprehensive and illustrative map which contributes to the understanding of professionals' involvement in research on ageing and health. A conceptual basis for further studies is offered, where the aim is to investigate the processes and outcomes entailed in involving professionals in research on ageing and health. The study also contributes to the development of instruments and theories for optimizing the involvement of professionals in research.